2011
DOI: 10.1007/s00148-011-0358-8
|View full text |Cite
|
Sign up to set email alerts
|

Kidnap risks and migration: evidence from Colombia

Abstract: Using a unique data set from the major Colombian cities collected between 2000-2003 and with information on more than 12,000 households, this paper studies the relationship between the kidnap risk a household faces with its migration decisions. We find evidence that exposure to such risk induces households to react sending some of their members to an international destination but not necessarily to a domestic one. Estimates are robust to the inclusion of several household characteristics usual in the migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Papers find that households with greater exposure to violence in their own or surrounding areas were more likely to move to safer metropolitan areas (Engel and Ibáñez, 2007), while households in major cities with higher kidnapping risks from rebel groups were likely to send members abroad (Rodriguez and Villa, 2012). The literature on Colombia also highlights that contrasted with traditional migration, risk aversion and lack of information may affect violence-induced migration (Engel and Ibáñez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Papers find that households with greater exposure to violence in their own or surrounding areas were more likely to move to safer metropolitan areas (Engel and Ibáñez, 2007), while households in major cities with higher kidnapping risks from rebel groups were likely to send members abroad (Rodriguez and Villa, 2012). The literature on Colombia also highlights that contrasted with traditional migration, risk aversion and lack of information may affect violence-induced migration (Engel and Ibáñez, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The perception of risk among migrants and refugees, however, might diverge significantly from the general population. The literature on migration choice is not unfamiliar to risk attitudes, and can instruct the design 9 See also Rodriguez and Villa (2012) for how displacement responds to changes in kidnapping risk, and Deschenes and Moretti (2009) for changes in mortality.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Empirical studies have shown that country-wide conflicts like the Cuban revolution and military takeovers in South America typically result in migration abroad, while localized areas of crime and violence lead to internal migration [37][38][39]. Ibáñez and Vélez [38] find evidence that crime and violence forced Colombians to migrate within the country, while Rodriguez and Villa [40] find evidence that the risk of kidnappings motivates households to send some of their members abroad. Recently in the US, the news media has reported extensively on the relatively recent outmigration of upper-middle and high income migrants from Mexico, the so-called "narco-refugees. "…”
Section: Network Health Crime and Migrationmentioning
confidence: 99%